PERANAN HUKUM ISLAM TERHADAP SISTEM PERKAWINAN ADAT KAILI DI KELURAHAN KABONENA KECAMATAN ULUJADI KOTA PALU - Megawati, Megawati (Katalogis, 2017)
The research studied about Kalili Customary Matrimonial Rites System practices prior to the entry of Islam in Kabonena Village, Ulujadi Sub-district, Palu City and the Roles of Islamic Law in Kaili Customary Matrimonial Rites System practices in Kabonena Village, Ulujadi Sub-district, Palu City. The objectives of the research were to identify the Practices in Kalili Customary Matrimonial Rites System prior to the entry of Islam in Kabonena Village, Ulujadi Sub-district, Palu City and the Roles of Islamic Law in Kalili Customary Matrimonial Rites System practices in Kabonena Village, Ulujadi Sub-district, Palu City. It was an empirical legal study using primary data and secondary data, represented in inductive reasoning, i.e.: concluded from specific issues into a general thought. The results of the research showed that the application of Islamic Law in Kalili Customary Matrimonial Rites System practices in Kabonena Village, Ulujadi Sub-district, Palu City was very tolerant, in the sense that the when Islamic law was adaptive to the customary law, it could adjust its existence. It was identified in customary matrimonial systemsÂ  gradually leaving some customary symbols.